The development of road transport: russian and foreign experience - E. Y. Rengold (Вестник СибАДИ, 2017)
The article is devoted to the study of the processes taking place in the trucking industry of Russia and developed countries of the world. It analyzes the statistical information in the field of road transport, considers the changes in Russian legislation in the sphere of transport, as well as analytical data on road transport, confirming the author's conclusions.